Export-Driven, Extensive Coastal Aquaculture Can Benefit Nutritionally Vulnerable People - Mamun, Abdullah-Al; Murray, Francis J.; Sprague, Matthew; McAdam, Bruce J.; Roos, Nanna; de Roos, Baukje; Pounds, Alexandra; Little, David C. (Frontiers in Sustainable Food Systems, 2021)
Export-orientated shrimp and prawn farming in coastal ghers has been associated with negative environmental, social and nutritional impacts. This study challenges these perceptions based on field observations from four communities in South West Bangladesh. Most households observed (>60%) were either directly involved in seafood farming or engaged elsewhere in the seafood value chain. Our study set out to establish how the type and location of aquaculture impacted on access to and consumption of aquatic animals. Additionally, we assessed the effects of both household socioeconomic status and intra-household food allocation on individual diet and nutritional outcomes. We used a blended approach, including a 24-hour consumption recall on two occasions, analysis of the proximate composition of aquatic animals and biomarkers from whole blood from a sample of the target population. The diverse polyculture systems generated broad social benefits, where ‘export-oriented’ production actually supplied more food locally than to global markets. Key findings: (1) worse-off households achieved higher productivity of farmed aquatic animals on smaller landholding than better-off households with larger landholdings; (2) vegetable production on gher dikes was a significant source of nutrition and income in lower saline gradients; (3) more fish was eaten in lower saline gradients although fish consumption was highly variable within and between households; (4) intra-household allocation of specific foods within diets were similar across communities; (5) recommended nutrient intakes of protein and zinc exceeded daily requirements for adolescent females, but energy, calcium and iron were below recommended intake levels (6) n-3 LC-PUFA, expressed as percentage of total fatty acids, in whole blood samples of adolescent females declined with ambient salinity level regardless of household socioeconomic status; (7) analysis of aquatic animals consumed found that mangrove species and tilapia harvested from higher saline ghers contained high levels of desirable PUFAs. These findings suggest that export-driven, extensive coastal aquaculture can be nutrition sensitive when co-products are retained for local consumption.